Multinationals in Russia and Ukraine in the face of war: The stakeholders' perspective - Monika Marcinkowska (Comparative Economic Research. Central and Eastern Europe, 2022)
The article categorises the attitudes of multinational corporations that do business in Russia (and Ukraine) in response to the war between the two countries from the perspective of the importance of their stakeholders. It also identifies the dimensions of responsibility to which the entity is committed. Eight types of strategies and four possible motives for the decision to adopt them are identified. Then, based on stakeholder theory, the companies' likely prioritisation of their primary interest groups in Russia and Ukraine is identified, and the dimensions of corporate responsibility that they perceive as key are identified. The analysis allows us to illustrate the background and consequences of the different strategies for the main stakeholders and indicate the firms' priorities and who has an impact on shaping their goals.
Keywords: M14; F23; F51; 330; Ukraine; Russia; war; stakeholders; corporate responsibility